2023
DOI: 10.3390/polym15061524
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Chitosan/Nano-Hydroxyapatite Composite for the Adsorptive Removal of Cd(II) from Aqueous Solution

Abstract: A novel polymer bio-composite based on nano-hydroxyapatite (n-Hap) and chitosan (CS) (CS/n-Hap) was synthesized to effectively address toxic cadmium ions removal from water. The composition and structure of CS/n-Hap bio-composite were analyzed through different characterization techniques. XRD patterns affirmed that the crystalline structure of n-Hap remained unaltered during CS/n-Hap synthesis, while FT-IR spectrum sustained all the characteristic peaks of both CS and n-Hap, affirming the successful synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(1 citation statement)
references
References 63 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…Polymeric materials for wastewater treatment applications are an area of interest. A study conducted by El Kaim Billah et al 45 reported the adsorption performance of chitosan-nHAp (C-nHAp) nanocomposite adsorbent. C-nHAp was prepared for the removal of Cd(II) ions from wastewater.…”
Section: Heavy Metal Removal Studiesmentioning
confidence: 99%
“…Polymeric materials for wastewater treatment applications are an area of interest. A study conducted by El Kaim Billah et al 45 reported the adsorption performance of chitosan-nHAp (C-nHAp) nanocomposite adsorbent. C-nHAp was prepared for the removal of Cd(II) ions from wastewater.…”
Section: Heavy Metal Removal Studiesmentioning
confidence: 99%